The Philosophical Analysis of the Future of Islamic Higher Education in Indonesia-Malaysia Facing Megatrend 2045 - Uswatun Hasanah; Zaki Faddad SZ (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2023)
In the era of megatrends, educational institutions must continue to make improvements, refinements, and changes in accordance with developments in order to maintain the quality of education and its existence, including Islamic higher education institutions. Therefore, this study aims to analyze philosophically the future of Islamic higher education in Indonesia and Malaysia facing Megatrend 2045. The method used is a descriptive-qualitative type of literature research with content analysis techniques. The results of the study show that ontologically, Islamic higher education in Indonesia-Malaysia needs to proactively respond to the megatrends of globalization, technological advancements, demographic changes, and sustainability. Emphasis should be place to maintain and develop a vision and mission based on pure and universal Islamic teachings while still contributing to the development of society and progress. In the realm of epistemology, Islamic higher education in Indonesia-Malaysia must continue to update learning and teaching methodologies in accordance with developments in science and technology, and axiologically, Islamic higher education in Indonesia-Malaysia must continue to promote moderate Islamic values. It can be concluded, a philosophical analysis provides a deeper understanding of the role, challenges, and strategies of Islamic higher education to maintain its existence and how Islamic teachings can make a significant contribution to facing future challenges.